(untitled) (Revista de Estudos em Municipalidade, 2026)
This study aimed to analyze the perception of power in managerial processes within organizations through a systematic literature review in the field of Administration, covering publications from 2014 to 2024. The investigation sought to understand how power is exercised, perceived, and interpreted in organizational contexts, using a qualitative methodology and rigorous criteria for selecting articles from the SPELL, Scopus, and Web of Science databases. A total of 32 articles were examined and organized into five thematic groups: forms of exercising power, interpersonal dynamics, decision-making processes, actors’ perceptions, and management regimes. The theoretical framework was based on classical authors such as Weber, French and Raven, Barnard, and Follett, as well as critical theorists including Foucault, Giddens, Clegg, and Mintzberg, enabling an understanding of power as domination, influence, cooperation, and productive relation. The results indicate that power manifests in symbolic, technical, disciplinary, and political forms, permeating formal structures and daily practices. Decision-making centralization and surveillance mechanisms were identified as recurrent instruments, especially in public organizations. The study concludes that power is a multifaceted phenomenon constitutive of organizational life, operating through both objective and subjective structures, and proposes a critical perspective of organizations as spaces where power is exercised, contested, and redefined.